Examining the Accuracy of Differenced One-Way Doppler Orbit Determination Derived from Range-Only Relay Satellite Tracking - Ashok Kumar Verma (Aerospace)
This paper delves into the impact of the Tracking and Data Relay Satellite (TDRS) constellation orbit accuracy on Differenced One-Way Doppler (DOWD)-based user spacecraft orbit determination, specifically when the TDRS orbit is derived solely from Telemetry, Tracking, and Command (TT&C) range-only tracking. The study revealed that retiring the Bilateration Ranging Transponder System (BRTS) without fully comprehending the TT&C bias and its uncertainty could hinder achieving the required level of orbit precision for both TDRS satellites (<75 m) and user spacecraft (<300 m). If the TT&C range bias and its associated uncertainties are not accurately calibrated in a TT&C-based TDRS orbit, it could lead to an orbit error of up to 17 km in the TDRS, yielding a DOWD-based orbit error of up to 5 km for the user spacecraft. The research identifies a linear relationship between TDRS orbit error and user spacecraft orbit error, with several factors impacting the slope of this relationship, including the number of DOWD passes obtained, the TDRS’s relative position during DOWD measurement acquisition, and dynamic errors in the user spacecraft orbit. Despite the imprecision in the orbits of the TDRS and user spacecraft, the Local Oscillator Frequency drift estimation remains accurate.